A FFM analysis on mode III static and fatigue crack initiation from sharp V-notches. (December 2021) - Campagnolo, Alberto; Sapora, Alberto
Highlights: The brittle failure initiation from sharp V-notches under mode III loading conditions is investigated. It is assumed that failure is shearing stress governed and that the crack initiates along the notch bisector plane. The coupled Finite Fracture Mechanics criterion is implemented semi-analytically. Modelling static fracture could be improved by considering nonlinear effects. The approach reveals promising in the fatigue framework. Abstract: The brittle or quasi-brittle failure initiation at sharp V-notches under mode III loading conditions is investigated by means of the coupled Finite Fracture Mechanics (FFM) approach. The model is developed by assuming that failure is shear stress governed, and by imposing a condition of consistency of both energy and stress requirements. The expression for the notch fracture toughness, which results a function of the material torsional strength, mode III fracture toughness and notch opening angle, is firstly derived. This allows to achieve the dimensionless failure stress through the analytical shape functions presented in the literature. By considering, as a general rule, the transition of fracture mechanism from tensile to shear in terms of the material strength ratio, experimental data referring to cylindrical V-notched samples are then discussed in the static regime. Although FFM predictions on the failure stress are fairly accurate, thus revealing simple tools for engineering purposes, a linear elastic analysis results simplistic since it disregards non linear effects (friction/ductility) observed during tests. Finally, the approach is extended to the fatigue framework, where the basic assumptions are proved to be more reliable. The analysis includes a discussion on the material properties to be implemented, and a satisfactory comparison with a large variety of experimental data.